Modified starch slurry and preparation method thereof
Through the combination and treatment of modified corn starch, wheat starch, potato starch and composite modified polyethylene wax nanoemulsion, a denatured starch slurry is formed, which solves the problem of reduced starch molecular chain flexibility and poor binding strength of inorganic materials, and achieves the effect of improving the mechanical properties and sizing ability of the starch.
Patent Information
- Application Number
- CN202411921431.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
AI Technical Summary
The reduction in the flexibility of the starch molecular chain affects the sizing, and the binding force of inorganic materials and starch is poor, easy to migrate and precipitate, affecting the use performance of starch.
Modified corn starch, wheat starch, potato starch and composite modified polyethylene wax nanoemulsion are used to form a denatured starch slurry through stirring and emulsification. The slurry is added to the coupling agent and emulsified oil to further improve its mechanical properties and stability.
The mechanical properties, wear resistance and sizing ability of the starch are improved, the stability and impact strength of the slurry are enhanced, and the performance is affected by the aggregation of nano-sized calcium phosphate oligomers.
Smart Images

Figure BDA0005208107340000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of modified starch slurry, in particular to a modified starch slurry and a preparation method thereof. Background Art
[0002] Starch is an abundant glucose-based polymer with good renewability, biodegradability and low cost. Therefore, it is widely used in the field of warp yarn sizing. Modified starch refers to the process of maintaining the inherent properties of the original starch by using physical, chemical or enzymatic treatment to change the size of starch molecules and particle properties or by introducing new functional groups to significantly change the starch properties. It is a modified starch with a porous honeycomb shape and special physical and chemical properties.
[0003] The molecular structure of starch contains a large number of hydroxyl groups and anhydroglucose ring structures. These hydroxyl groups can cause the molecular chains to associate and form hydrogen bonds. The ring structure can reduce the flexibility of the starch molecular chains, making them easy to break and fall off from the warp yarn surface, severely limiting their application in textile sizing. By modifying starch and compounding it with organic and inorganic materials, the wear resistance and mechanical properties of starch can be effectively improved. However, organic and inorganic materials have poor binding force with starch and are easy to migrate and precipitate, affecting the performance of starch. Summary of the invention
[0004] The invention provides a modified starch slurry and a preparation method thereof, which solves the problems that the flexibility of starch molecular chains decreases and affects sizing, and that inorganic materials have poor binding force with starch and are easy to migrate and precipitate.
[0005] The technical solution of the present invention:
[0006] A modified starch slurry comprises the following raw materials in parts by weight: 50-60 parts of modified corn starch, 20-30 parts of wheat starch, 25-35 parts of potato starch, 10-15 parts of composite modified polyethylene wax nanoemulsion, 2-4 parts of coupling agent, and 4-5 parts of emulsified oil;
[0007] A method for preparing a modified starch slurry comprises the following preparation steps:
[0008] Modified corn starch, wheat starch, potato starch, composite modified polyethylene wax nanoemulsion, coupling agent and emulsified oil are mixed, stirred at 75-85° C. for 20-30 minutes, then emulsified oil and coupling agent are added, stirred at a speed of 300-400 r / min for 20-30 minutes to obtain modified starch slurry.
[0009] The composite modified polyethylene wax nanoemulsion is prepared by a mixed reaction of modified carboxylated cellulose nanofibers and maleic anhydride grafted polyethylene wax;
[0010] The modified carboxylated cellulose nanofibers are prepared by a mixed reaction of calcium chloride, an ethanol solution of phosphoric acid and carboxylated cellulose nanofibers;
[0011] The modified corn starch is obtained by mixing amylase and corn starch for reaction, and then mixing with curcumin and tannic acid.
[0012] Furthermore, the coupling agent is γ-aminopropyltriethoxysilane.
[0013] Furthermore, the composite modified polyethylene wax nanoemulsion is specifically prepared by the following steps:
[0014] A1. Add phosphoric acid to ethanol and stir to obtain an ethanol solution of phosphoric acid, add calcium chloride dihydrate to ethanol and stir to obtain a modified carboxylated cellulose nanofiber by adding triethylamine and carboxylated cellulose nanofibers and stirring to obtain a modified carboxylated cellulose nanofiber by adding the ethanol solution of phosphoric acid, stirring and reacting at 20-30° C. for 10-12 hours, centrifuging, washing and drying to obtain a modified carboxylated cellulose nanofiber;
[0015] A2. The maleic anhydride grafted polyethylene wax and sodium hydroxide were added to deionized water, stirred evenly, placed in a reactor, introduced nitrogen, heated to 140-150 ° C, stirred at 800-900r / min for 0.5-1.5h, cooled to room temperature, filtered, and a polyethylene wax nanoemulsion was obtained;
[0016] A3. Add 10 g of modified carboxylated cellulose nanofibers to 100 mL of polyethylene wax nanoemulsion, heat to 140-150° C., stir at 800-900 r / min for 0.5-1.5 h, and cool to room temperature to obtain a composite modified polyethylene wax nanoemulsion.
[0017] Furthermore, during the above-mentioned A1 reaction process, the oxygen-containing functional groups contained on the surface of the carboxylated cellulose nanofibers can combine with the calcium ions in the calcium chloride dihydrate, so that the calcium ions are deposited on the surface of the carboxylated cellulose nanofibers, and the phosphate ions provided by the phosphoric acid can combine with the calcium ions deposited on the surface of the carboxylated cellulose nanofibers to form a calcium phosphate complex, and triethylamine can control the release rate of calcium ions in the calcium nitrate. As the reaction proceeds, the calcium phosphate oligomers crystallize and grow on the surface of the carboxylated cellulose nanofibers, so that the calcium phosphate oligomers are coated on the surface of the carboxylated cellulose to form modified carboxylated cellulose nanofibers.
[0018] Furthermore, in the above-mentioned reaction A2, the carboxyl group of maleic anhydride in the maleic anhydride grafted polyethylene wax undergoes a saponification reaction with sodium hydroxide, and the carboxyl group after the anhydride ring opening is equivalent to a hydrophilic group. The polyethylene wax molecules act as a surfactant, which is equivalent to a lipophilic group, and then self-emulsify into a polyethylene wax nanoemulsion.
[0019] Furthermore, during the above-mentioned A3 reaction process, the calcium phosphate oligomer contained on the surface of the modified carboxylated cellulose nanofibers can be chemically bonded to the carboxyl groups after the anhydride ring opening in the polyethylene wax nanoemulsion, so that the modified carboxylated cellulose nanofibers are dispersed in the polyethylene wax nanoemulsion to form a composite modified polyethylene wax nanoemulsion.
[0020] Furthermore, in step A1, the ratio of phosphoric acid to ethanol is (2-3) g:(15-25) mL.
[0021] Furthermore, in step A1, the ratio of calcium chloride dihydrate, ethanol, triethylamine, carboxylated cellulose nanofibers and ethanol solution of phosphoric acid is (4-5) g: (45-55) mL: (6-7) mL: (7-8) g: (5-6) mL.
[0022] Furthermore, in step A2, the ratio of the maleic anhydride grafted polyethylene wax, sodium hydroxide and deionized water is (2-3) g: (1-2) g: (45-55) mL.
[0023] Furthermore, in step A3, the ratio of the modified carboxylated cellulose nanofibers to the polyethylene wax nanoemulsion is (8-12) g:(90-120) mL.
[0024] Furthermore, the modified corn starch is specifically prepared by the following steps:
[0025] B1. Add corn starch to sodium phosphate buffer, stir evenly, add α-amylase and amyloglucosidase, and after enzymolysis, add sodium hydroxide solution, stir to kill the enzyme, centrifuge and dry to obtain porous starch;
[0026] B2. Add curcumin and tannic acid to deionized water, stir evenly, add porous starch, shake at a rate of 120-130 r / min for 1-2 hours, centrifuge, and dry to obtain modified corn starch.
[0027] Furthermore, during the above-mentioned B1 reaction process, α-amylase and amyloglucosidase undergo enzymatic hydrolysis reaction with corn starch, extending from the surface of corn starch granules to the interior of the starch. After the enzymatic hydrolysis reaction is completed, the enzymatic hydrolysis products are removed, so that the corn starch forms a porous structure.
[0028] Furthermore, during the above-mentioned B2 reaction process, the porous corn starch has a large specific surface area and excellent adsorption performance, and can adsorb curcumin and tannic acid. The oxygen-containing functional groups contained in curcumin and tannic acid can be combined with the hydroxyl groups of the porous starch through hydrogen bonds, so that curcumin and tannic acid are adsorbed on the pores and surface of the porous starch to form modified corn starch.
[0029] Furthermore, in step B1, the amount ratio of corn starch, sodium phosphate buffer, α-amylase, amyloglucosidase and sodium hydroxide solution is (25-35) g: (80-120) mL: (0.1-0.3) g: (0.2-0.4) g: (4-6) mL.
[0030] Furthermore, in step B2, the ratio of curcumin, tannic acid, deionized water and porous corn starch is (2-3) g: (2-2.4) g: (25-35) mL: (8-9) g.
[0031] The present invention has the following beneficial effects:
[0032] (1) In the technical scheme of the present invention, calcium phosphate oligomers are formed on the surface of carboxylated cellulose. Carboxylated cellulose nanofibers have a high specific surface area and can load more calcium phosphate oligomers, thereby avoiding the agglomeration of nano-sized calcium phosphate oligomers to affect the performance of modified starch slurry. Calcium phosphate oligomers have high wear resistance and mechanical strength, and are combined with carboxylated cellulose nanofibers to improve the mechanical properties and wear resistance of modified starch slurry and improve the sizing ability of starch. In addition, the carboxylated cellulose nanofibers are randomly distributed in the modified starch slurry and interact with the modified starch, so that the modified starch forms a more stable structure, thereby improving the stability of the slurry. The randomly distributed carboxylated cellulose nanofibers can absorb external stress and improve the impact strength of the modified starch slurry.
[0033] (2) In the technical scheme of the present invention, modified carboxylated cellulose nanofibers are dispersed in polyethylene wax nanoemulsion to form a composite modified polyethylene wax nanoemulsion with a cross-linked network structure, and an organic-inorganic cross-linked network structure is constructed and dispersed in a modified starch slurry, so that the modified starch slurry has ultra-high wear resistance, toughness and mechanical strength, and improves the sizing ability of starch. The composite modified polyethylene wax nanoemulsion has good flowability and can enter the pores of porous starch, and then is evenly dispersed in the modified starch slurry to enhance the performance of the modified starch.
[0034] (3) In the technical solution of the present invention, corn starch forms a porous structure with excellent adsorption performance, and can adsorb curcumin and tannic acid on the pores and surface of the porous starch. Curcumin and tannic acid serve as the supporting skeleton of the porous starch, thereby improving the impact resistance and toughness of the porous starch and the sizing performance of the modified starch slurry. In addition, curcumin and tannic acid are cross-linked with each other to form a cross-linked network structure, which has a good adsorption effect on the additives adsorbed into the porous corn starch, so that the additives are more firmly combined in the modified starch slurry, thereby improving the performance of the starch. DETAILED DESCRIPTION
[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] The raw materials used in the examples of the present invention are as follows, and all reagents used are of analytical grade.
[0037] Among them, corn starch, food grade, moisture content 14.2%, apparent viscosity 46mPa·s, provided by Shandong Hengren Industry and Trade Co., Ltd.
[0038] Wheat starch: food grade, Xinxiang Liangrun Whole Grain Food Co., Ltd.
[0039] Potato starch: food grade, Shanghai Lvsheng Industrial Co., Ltd.
[0040] The carboxylated cellulose nanofibers have a diameter of 8 nm and a length of 2 μm, and were provided by Guilin Qihong Technology Co., Ltd.
[0041] The coupling agent is γ-aminopropyltriethoxysilane.
[0042] Example 1
[0043] A modified starch slurry comprises the following raw materials in parts by weight: 50 parts of modified corn starch, 20 parts of wheat starch, 25 parts of potato starch, 10 parts of composite modified polyethylene wax nanoemulsion, 2 parts of γ-aminopropyltriethoxysilane, and 4 parts of emulsified oil;
[0044] A method for preparing a modified starch slurry comprises the following preparation steps:
[0045] Modified corn starch, wheat starch, potato starch, composite modified polyethylene wax nanoemulsion, coupling agent and emulsified oil were mixed, stirred at 75°C for 20 minutes, and then emulsified oil and γ-aminopropyltriethoxysilane were added, and stirred at a speed of 300 r / min for 20 minutes to obtain modified starch slurry.
[0046] The composite modified polyethylene wax nanoemulsion is specifically prepared by the following steps:
[0047] A1. Add 2 g of phosphoric acid to 15 mL of ethanol and stir to obtain an ethanol solution of phosphoric acid. Add 4 g of calcium chloride dihydrate to 45 mL of ethanol and stir to obtain an ethanol solution of phosphoric acid. Add 6 mL of triethylamine and 7 g of carboxylated cellulose nanofibers and continue stirring for 10 min. Add 5 mL of the ethanol solution of phosphoric acid and stir at 20 ° C for 10 h. Centrifuge at 8000 r / min for 5 min to remove triethylamine. Wash with ethanol 3 times, wash with deionized water 3 times, and dry in an oven at 50 ° C for 10 min to obtain modified carboxylated cellulose nanofibers.
[0048] A2. 2 g of maleic anhydride grafted polyethylene wax and 1 g of sodium hydroxide were added to 45 mL of deionized water, stirred evenly, placed in a reactor, nitrogen was introduced to exhaust the air, the temperature was raised to 140 ° C, stirred at 800 r / min for 0.5 h, cooled to room temperature, filtered, and a polyethylene wax nanoemulsion was obtained;
[0049] A3. Add 8 g of modified carboxylated cellulose nanofibers to 80 mL of polyethylene wax nanoemulsion, heat to 140°C, stir at 800 r / min for 0.5 h, and cool to room temperature to obtain a composite modified polyethylene wax nanoemulsion.
[0050] Modified corn starch is specifically prepared by the following steps:
[0051] B1. 25 g corn starch was added to 80 mL of 0.1 M sodium phosphate buffer, stirred at 30 ° C for 15 min, 0.1 g α-amylase and 0.2 g amyloglucosidase were added, and the mixture was placed in a 55 ° C water bath at a speed of 180 rpm for 10 h, 4 mL of 2 M sodium hydroxide solution was added, stirred for 10 min to kill the enzyme, and then centrifuged at 2000 r / min for 10 min to remove ethanol, and dried in an oven at 40 ° C for 30 min to obtain porous starch;
[0052] B2. Add 2 g of curcumin and 2 g of tannic acid to 25 mL of deionized water, stir evenly, add 8 g of porous starch, shake at 120 r / min for 1 h, centrifuge at 3000 r / min for 10 min to obtain a solid, and dry the solid in an oven at 40°C for 30 min to obtain modified corn starch.
[0053] Example 2
[0054] A modified starch slurry comprises the following raw materials in parts by weight: 55 parts of modified corn starch, 25 parts of wheat starch, 30 parts of potato starch, 13 parts of composite modified polyethylene wax nanoemulsion, 3 parts of γ-aminopropyltriethoxysilane, and 4.5 parts of emulsified oil;
[0055] A method for preparing a modified starch slurry comprises the following preparation steps:
[0056] Modified corn starch, wheat starch, potato starch, composite modified polyethylene wax nanoemulsion, coupling agent and emulsified oil were mixed, stirred at 80°C for 25 minutes, and then emulsified oil and γ-aminopropyltriethoxysilane were added, and stirred at a speed of 350 r / min for 25 minutes to obtain modified starch slurry.
[0057] The composite modified polyethylene wax nanoemulsion is specifically prepared by the following steps:
[0058] A1. Add 2.5 g of phosphoric acid to 20 mL of ethanol and stir to obtain an ethanol solution of phosphoric acid. Add 4.5 g of calcium chloride dihydrate to 50 mL of ethanol and stir to obtain an ethanol solution of phosphoric acid. Add 6.5 mL of triethylamine and 7.5 g of carboxylated cellulose nanofibers and continue stirring for 10 min. Add 5.5 mL of the ethanol solution of phosphoric acid and stir at 25 ° C for 11 h. Centrifuge at 8000 r / min for 5 min to remove triethylamine. Wash with ethanol 3 times, wash with deionized water 3 times, and dry in an oven at 50 ° C for 10 min to obtain modified carboxylated cellulose nanofibers.
[0059] A2. 2.5 g of maleic anhydride grafted polyethylene wax and 1.5 g of sodium hydroxide were added to 50 mL of deionized water, stirred evenly, placed in a reactor, nitrogen was introduced and the air was exhausted, the temperature was raised to 145 ° C, stirred at 850 r / min for 1 h, cooled to room temperature, filtered, and a polyethylene wax nanoemulsion was obtained;
[0060] A3. Add 10 g of modified carboxylated cellulose nanofibers to 100 mL of polyethylene wax nanoemulsion, heat to 145° C., stir at 850 r / min for 1 h, and cool to room temperature to obtain a composite modified polyethylene wax nanoemulsion.
[0061] Modified corn starch is specifically prepared by the following steps:
[0062] B1. 30 g corn starch was added to 100 mL of 0.1 M sodium phosphate buffer, stirred at 30 ° C for 15 min, 0.2 g α-amylase and 0.3 g amyloglucosidase were added, and the mixture was placed in a 55 ° C water bath at a speed of 180 rpm for 10 h, 5 mL of 2 M sodium hydroxide solution was added, stirred for 10 min to kill the enzyme, and then centrifuged at 2000 r / min for 10 min to remove ethanol, and dried in an oven at 40 ° C for 30 min to obtain porous starch;
[0063] B2. Add 2.5 g of curcumin and 2.2 g of tannic acid to 30 mL of deionized water, stir evenly, add 8.5 g of porous starch, shake at a rate of 125 r / min for 1.5 h, centrifuge at 3000 r / min for 10 min to obtain a solid, and dry the solid in an oven at 40°C for 30 min to obtain modified corn starch.
[0064] Example 3
[0065] A modified starch slurry comprises the following raw materials in parts by weight: 60 parts of modified corn starch, 30 parts of wheat starch, 35 parts of potato starch, 15 parts of composite modified polyethylene wax nanoemulsion, 4 parts of γ-aminopropyltriethoxysilane, and 5 parts of emulsified oil;
[0066] A method for preparing a modified starch slurry comprises the following preparation steps:
[0067] Modified corn starch, wheat starch, potato starch, composite modified polyethylene wax nanoemulsion, coupling agent and emulsified oil were mixed, stirred at 85° C. for 30 min, emulsified oil and γ-aminopropyltriethoxysilane were added, and stirred at a rate of 400 r / min for 30 min to obtain modified starch slurry.
[0068] The composite modified polyethylene wax nanoemulsion is specifically prepared by the following steps:
[0069] A1. Add 3 g of phosphoric acid to 25 mL of ethanol and stir to obtain an ethanol solution of phosphoric acid. Add 5 g of calcium chloride dihydrate to 55 mL of ethanol and stir to obtain an ethanol solution of phosphoric acid. Add 7 mL of triethylamine and 8 g of carboxylated cellulose nanofibers and continue stirring for 10 min. Add 6 mL of the ethanol solution of phosphoric acid and stir at 30 ° C for 12 h. Centrifuge at 8000 r / min for 5 min to remove triethylamine. Wash with ethanol 3 times, wash with deionized water 3 times, and dry in an oven at 50 ° C for 10 min to obtain modified carboxylated cellulose nanofibers.
[0070] A2. 3 g of maleic anhydride grafted polyethylene wax and 2 g of sodium hydroxide were added to 45 mL of deionized water, stirred evenly, placed in a reactor, nitrogen was introduced and the air was exhausted, the temperature was raised to 150 ° C, stirred at 900 r / min for 1.5 h, cooled to room temperature, filtered, and a polyethylene wax nanoemulsion was obtained;
[0071] A3. Add 12 g of modified carboxylated cellulose nanofibers to 120 mL of polyethylene wax nanoemulsion, heat to 150° C., stir at 900 r / min for 1.5 h, and cool to room temperature to obtain a composite modified polyethylene wax nanoemulsion.
[0072] Modified corn starch is specifically prepared by the following steps:
[0073] B1. 35 g corn starch was added to 120 mL of 0.1 M sodium phosphate buffer, stirred at 30 ° C for 15 min, 0.3 g α-amylase and 0.4 g amyloglucosidase were added, and the mixture was placed in a 55 ° C water bath at a speed of 180 rpm for 10 h, 6 mL of 2 M sodium hydroxide solution was added, stirred for 10 min to kill the enzyme, and then centrifuged at 2000 r / min for 10 min to remove ethanol, and dried in an oven at 40 ° C for 30 min to obtain porous starch;
[0074] B2. Add 3 g of curcumin and 2.4 g of tannic acid to 35 mL of deionized water, stir evenly, add 9 g of porous starch, shake at a rate of 130 r / min for 2 h, centrifuge at 3000 r / min for 10 min to obtain a solid, and dry the solid in an oven at 40°C for 30 min to obtain modified corn starch.
[0075] Comparative Example 1
[0076] A modified starch slurry comprises the following raw materials in parts by weight: 60 parts of modified corn starch, 30 parts of wheat starch, 35 parts of potato starch, 15 parts of composite modified polyethylene wax nanoemulsion, 4 parts of γ-aminopropyltriethoxysilane, and 5 parts of emulsified oil;
[0077] A method for preparing a modified starch slurry comprises the following preparation steps:
[0078] Modified corn starch, wheat starch, potato starch, composite modified polyethylene wax nanoemulsion, coupling agent and emulsified oil were mixed, stirred at 85° C. for 30 min, emulsified oil and γ-aminopropyltriethoxysilane were added, and stirred at a rate of 400 r / min for 30 min to obtain modified starch slurry.
[0079] The composite modified polyethylene wax nanoemulsion is specifically prepared by the following steps:
[0080] A1. 3 g of maleic anhydride grafted polyethylene wax and 2 g of sodium hydroxide were added to 45 mL of deionized water, stirred evenly, placed in a reactor, nitrogen was introduced to exhaust the air, the temperature was raised to 150 ° C, stirred at 900 r / min for 1.5 h, cooled to room temperature, filtered, and a polyethylene wax nanoemulsion was obtained;
[0081] A2. Add 12 g of carboxylated cellulose nanofibers to 120 mL of polyethylene wax nanoemulsion, heat to 150° C., stir at 900 r / min for 1.5 h, and cool to room temperature to obtain a composite modified polyethylene wax nanoemulsion.
[0082] Modified corn starch is specifically prepared by the following steps:
[0083] B1. 35 g corn starch was added to 120 mL of 0.1 M sodium phosphate buffer, stirred at 30 ° C for 15 min, 0.3 g α-amylase and 0.4 g amyloglucosidase were added, and the mixture was placed in a 55 ° C water bath at a speed of 180 rpm for 10 h, 6 mL of 2 M sodium hydroxide solution was added, stirred for 10 min to kill the enzyme, and then centrifuged at 2000 r / min for 10 min to remove ethanol, and dried in an oven at 40 ° C for 30 min to obtain porous starch;
[0084] B2. Add 3 g of curcumin and 2.4 g of tannic acid to 35 mL of deionized water, stir evenly, add 9 g of porous starch, shake at a rate of 130 r / min for 2 h, centrifuge at 3000 r / min for 10 min to obtain a solid, and dry the solid in an oven at 40°C for 30 min to obtain modified corn starch.
[0085] Comparative Example 2
[0086] A modified starch slurry comprises the following raw materials in parts by weight: 60 parts of modified corn starch, 30 parts of wheat starch, 35 parts of potato starch, 15 parts of composite modified polyethylene wax nanoemulsion, 4 parts of γ-aminopropyltriethoxysilane, and 5 parts of emulsified oil;
[0087] A method for preparing a modified starch slurry comprises the following preparation steps:
[0088] Modified corn starch, wheat starch, potato starch, composite modified polyethylene wax nanoemulsion, coupling agent and emulsified oil were mixed, stirred at 85° C. for 30 min, emulsified oil and γ-aminopropyltriethoxysilane were added, and stirred at a rate of 400 r / min for 30 min to obtain modified starch slurry.
[0089] The composite modified polyethylene wax nanoemulsion is specifically prepared by the following steps:
[0090] A1. Add 3 g of phosphoric acid to 25 mL of ethanol and stir to obtain an ethanol solution of phosphoric acid. Add 5 g of calcium chloride dihydrate to 55 mL of ethanol and stir to obtain an ethanol solution of phosphoric acid. Add 7 mL of triethylamine and continue stirring for 10 min. Add 6 mL of the ethanol solution of phosphoric acid and stir at 30°C for 12 h. Centrifuge at 8000 r / min for 5 min to remove triethylamine. Wash with ethanol 3 times, wash with deionized water 3 times, and dry in an oven at 50°C for 10 min to obtain calcium phosphate oligomers.
[0091] A2. 3 g of maleic anhydride grafted polyethylene wax and 2 g of sodium hydroxide were added to 45 mL of deionized water, stirred evenly, placed in a reactor, nitrogen was introduced and the air was exhausted, the temperature was raised to 150 ° C, stirred at 900 r / min for 1.5 h, cooled to room temperature, filtered, and a polyethylene wax nanoemulsion was obtained;
[0092] A3. Add 12 g of calcium phosphate oligomer to 120 mL of polyethylene wax nanoemulsion, heat to 150° C., stir at 900 r / min for 1.5 h, and cool to room temperature to obtain a composite modified polyethylene wax nanoemulsion.
[0093] Modified corn starch is specifically prepared by the following steps:
[0094] B1. 35 g corn starch was added to 120 mL of 0.1 M sodium phosphate buffer, stirred at 30 ° C for 15 min, 0.3 g α-amylase and 0.4 g amyloglucosidase were added, and the mixture was placed in a 55 ° C water bath at a speed of 180 rpm for 10 h, 6 mL of 2 M sodium hydroxide solution was added, stirred for 10 min to kill the enzyme, and then centrifuged at 2000 r / min for 10 min to remove ethanol, and dried in an oven at 40 ° C for 30 min to obtain porous starch;
[0095] B2. Add 3 g of curcumin and 2.4 g of tannic acid to 35 mL of deionized water, stir evenly, add 9 g of porous starch, shake at a rate of 130 r / min for 2 h, centrifuge at 3000 r / min for 10 min to obtain a solid, and dry the solid in an oven at 40°C for 30 min to obtain modified corn starch.
[0096] Comparative Example 3
[0097] A modified starch slurry comprises the following raw materials in parts by weight: 60 parts of modified corn starch, 30 parts of wheat starch, 35 parts of potato starch, 15 parts of composite modified polyethylene wax nanoemulsion, 4 parts of γ-aminopropyltriethoxysilane, and 5 parts of emulsified oil;
[0098] A method for preparing a modified starch slurry comprises the following preparation steps:
[0099] Modified corn starch, wheat starch, potato starch, composite modified polyethylene wax nanoemulsion, coupling agent and emulsified oil were mixed, stirred at 85° C. for 30 min, emulsified oil and γ-aminopropyltriethoxysilane were added, and stirred at a rate of 400 r / min for 30 min to obtain modified starch slurry.
[0100] The composite modified polyethylene wax nanoemulsion is specifically prepared by the following steps:
[0101] A1. Add 3 g of phosphoric acid to 25 mL of ethanol and stir to obtain an ethanol solution of phosphoric acid. Add 5 g of calcium chloride dihydrate to 55 mL of ethanol and stir to obtain an ethanol solution of phosphoric acid. Add 7 mL of triethylamine and 8 g of carboxylated cellulose nanofibers and continue stirring for 10 min. Add 6 mL of the ethanol solution of phosphoric acid and stir at 30 ° C for 12 h. Centrifuge at 8000 r / min for 5 min to remove triethylamine. Wash with ethanol 3 times, wash with deionized water 3 times, and dry in an oven at 50 ° C for 10 min to obtain modified carboxylated cellulose nanofibers.
[0102] A2. 3 g of maleic anhydride grafted polyethylene wax and 2 g of sodium hydroxide were added to 45 mL of deionized water, stirred evenly, placed in a reactor, nitrogen was introduced and the air was exhausted, the temperature was raised to 150 ° C, stirred at 900 r / min for 1.5 h, cooled to room temperature, filtered, and a polyethylene wax nanoemulsion was obtained;
[0103] A3. Add 12 g of modified carboxylated cellulose nanofibers to 120 mL of polyethylene wax nanoemulsion, heat to 150° C., stir at 900 r / min for 1.5 h, and cool to room temperature to obtain a composite modified polyethylene wax nanoemulsion.
[0104] Modified corn starch is specifically prepared by the following steps:
[0105] B1. 35 g corn starch was added to 120 mL of 0.1 M sodium phosphate buffer, stirred at 30 ° C for 15 min, 0.3 g α-amylase and 0.4 g amyloglucosidase were added, and the mixture was placed in a 55 ° C water bath at a speed of 180 rpm for 10 h, 6 mL of 2 M sodium hydroxide solution was added, stirred for 10 min to kill the enzyme, and then centrifuged at 2000 r / min for 10 min to remove ethanol, and dried in an oven at 40 ° C for 30 min to obtain porous starch;
[0106] B2. Add 3 g of curcumin to 35 mL of deionized water, stir evenly, add 9 g of porous starch, shake at a rate of 130 r / min for 2 h, centrifuge at 3000 r / min for 10 min to obtain a solid, and dry the solid in an oven at 40°C for 30 min to obtain modified corn starch.
[0107] Comparative Example 4
[0108] A modified starch slurry comprises the following raw materials in parts by weight: 60 parts of modified corn starch, 30 parts of wheat starch, 35 parts of potato starch, 15 parts of composite modified polyethylene wax nanoemulsion, 4 parts of γ-aminopropyltriethoxysilane, and 5 parts of emulsified oil;
[0109] A method for preparing a modified starch slurry comprises the following preparation steps:
[0110] Modified corn starch, wheat starch, potato starch, composite modified polyethylene wax nanoemulsion, coupling agent and emulsified oil were mixed, stirred at 85° C. for 30 min, emulsified oil and γ-aminopropyltriethoxysilane were added, and stirred at a rate of 400 r / min for 30 min to obtain modified starch slurry.
[0111] The composite modified polyethylene wax nanoemulsion is specifically prepared by the following steps:
[0112] A1. Add 3 g of phosphoric acid to 25 mL of ethanol and stir to obtain an ethanol solution of phosphoric acid. Add 5 g of calcium chloride dihydrate to 55 mL of ethanol and stir to obtain an ethanol solution of phosphoric acid. Add 7 mL of triethylamine and 8 g of carboxylated cellulose nanofibers and continue stirring for 10 min. Add 6 mL of the ethanol solution of phosphoric acid and stir at 30 ° C for 12 h. Centrifuge at 8000 r / min for 5 min to remove triethylamine. Wash with ethanol 3 times, wash with deionized water 3 times, and dry in an oven at 50 ° C for 10 min to obtain modified carboxylated cellulose nanofibers.
[0113] A2. 3 g of maleic anhydride grafted polyethylene wax and 2 g of sodium hydroxide were added to 45 mL of deionized water, stirred evenly, placed in a reactor, nitrogen was introduced and the air was exhausted, the temperature was raised to 150 ° C, stirred at 900 r / min for 1.5 h, cooled to room temperature, filtered, and a polyethylene wax nanoemulsion was obtained;
[0114] A3. Add 12 g of modified carboxylated cellulose nanofibers to 120 mL of polyethylene wax nanoemulsion, heat to 150° C., stir at 900 r / min for 1.5 h, and cool to room temperature to obtain a composite modified polyethylene wax nanoemulsion.
[0115] Modified corn starch is specifically prepared by the following steps:
[0116] B1. 35 g corn starch was added to 120 mL of 0.1 M sodium phosphate buffer, stirred at 30 ° C for 15 min, 0.3 g α-amylase and 0.4 g amyloglucosidase were added, and the mixture was placed in a 55 ° C water bath at a speed of 180 rpm for 10 h, 6 mL of 2 M sodium hydroxide solution was added, stirred for 10 min to kill the enzyme, and then centrifuged at 2000 r / min for 10 min to remove ethanol, and dried in an oven at 40 ° C for 30 min to obtain porous starch;
[0117] B2. Add 3 g of curcumin to 35 mL of deionized water, stir evenly, add 9 g of porous starch, shake at a rate of 130 r / min for 2 h, centrifuge at 3000 r / min for 10 min to obtain a solid, and dry the solid in an oven at 40°C for 30 min to obtain modified corn starch.
[0118] The performance of the modified starch slurries prepared in Examples 1-3 and Comparative Examples 1-4 was tested.
[0119] Slurry surface tension test: The modified starch slurry prepared above was tested on an A60 / A80 automatic surface tension meter to determine the surface tension of the modified starch slurry.
[0120] Test of breaking strength and elongation at break of slurry: Pour the modified starch slurry prepared as above onto a glass plate sandwiched between a polyester film and a polyester frame, scrape the slurry flat with a steel ruler, dry it under constant temperature and humidity conditions of 65% and 20°C, cut a 200mm×10mm slurry film, and test its breaking strength and elongation at break on a YG065H multifunctional electronic fabric strength tester (clamp distance of 100mm, stretching speed of 500mm / min).
[0121] Sizing rate detection: 32S pure cotton yarn was immersed in the modified starch slurry prepared above, immersed at 95°C for 5 minutes, then taken out and dried naturally. The dried yarn was placed at 25°C and 65% humidity for 24 hours, and the mass after sizing was measured. The 32S pure cotton yarn was recorded as W1, and the mass of the yarn after sizing was recorded as W2. The sizing rate = (W2-W1) / W1×100%.
[0122] Wear resistance test: The sizing yarn was subjected to a reciprocating friction test using a YG109 yarn wear tester. A load of 25 g was applied to each sample, the wear rate was 60 times / min, the sandpaper specification was 80 mesh, and the wear times were recorded; as shown in Table 1 below.
[0123] Table 1 Performance test of modified starch slurry prepared in Examples 1-3 and Comparative Examples 1-4
[0124]
[0125] It can be seen from the data in Table 1 that the highly elastic polyvinyl chloride materials prepared in Examples 1-3 have a high elastic modulus and mechanical strength. In Comparative Example 1, the modified carboxylated cellulose nanofibers were replaced with a composite modified polyethylene wax nanoemulsion prepared from carboxylated cellulose nanofibers and added to the modified starch slurry, and its mechanical properties and sizing properties decreased, proving that calcium phosphate oligomers were formed on the surface of the carboxylated cellulose, which had high wear resistance and mechanical strength.
[0126] In Comparative Example 2, the composite modified polyethylene wax nanoemulsion prepared without adding carboxylated cellulose nanofibers was added to the modified starch slurry, and its mechanical properties and sizing properties decreased, indicating that the carboxylated cellulose nanofibers were randomly distributed in the modified starch slurry, which improved the stability of the slurry, and the random distribution of the carboxylated cellulose nanofibers could absorb external stress, improve the impact strength of the modified starch slurry, construct an organic-inorganic cross-linked network structure, and be dispersed in the modified starch slurry, so that the modified starch slurry has ultra-high wear resistance, toughness and mechanical strength, and improves the sizing ability of starch.
[0127] The modified corn starch prepared without adding curcumin in Comparative Example 3 was added to the modified starch slurry, and its mechanical properties and sizing properties decreased, indicating that curcumin and tannic acid were the supporting skeleton of porous starch, which improved the impact resistance and toughness of porous starch and the sizing properties of modified starch slurry.
[0128] The modified corn starch prepared without adding tannic acid in Comparative Example 4 was added to the modified starch slurry, and its mechanical properties and sizing properties decreased, proving that curcumin and tannic acid were cross-linked with each other to form a cross-linked network structure, which had a good adsorption effect on the additive adsorbed into the porous corn starch, making the additive more firmly combined in the modified starch slurry, thereby improving the performance of the starch.
[0129] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0130] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A modified starch slurry, characterized in that: The invention comprises the following raw materials in parts by weight: 50-60 parts of modified corn starch, 20-30 parts of wheat starch, 25-35 parts of potato starch, 10-15 parts of composite modified polyethylene wax nanoemulsion, 2-4 parts of coupling agent and 4-5 parts of emulsified oil; The composite modified polyethylene wax nanoemulsion is prepared by a mixed reaction of modified carboxylated cellulose nanofibers and maleic anhydride grafted polyethylene wax; The modified carboxylated cellulose nanofibers are prepared by a mixed reaction of calcium chloride, an ethanol solution of phosphoric acid and carboxylated cellulose nanofibers; The modified corn starch is obtained by mixing amylase and corn starch for reaction, and then mixing with curcumin and tannic acid.
2. A modified starch slurry according to claim 1, characterized in that: The composite modified polyethylene wax nanoemulsion is specifically prepared by the following steps: A1. Add phosphoric acid to ethanol and stir to obtain an ethanol solution of phosphoric acid, add calcium chloride dihydrate to ethanol and stir to obtain a modified carboxylated cellulose nanofiber by adding triethylamine and carboxylated cellulose nanofibers and stirring to obtain a modified carboxylated cellulose nanofiber by adding the ethanol solution of phosphoric acid, stirring at 20-30° C. for 10-12 hours, centrifuging, washing and drying to obtain a modified carboxylated cellulose nanofiber; A2. The maleic anhydride grafted polyethylene wax and sodium hydroxide were added to deionized water, stirred evenly, placed in a reactor, introduced nitrogen, heated to 140-150 ° C, stirred at 800-900r / min for 0.5-1.5h, cooled to room temperature, filtered, and a polyethylene wax nanoemulsion was obtained; A3. Add 10 g of modified carboxylated cellulose nanofibers to 100 mL of polyethylene wax nanoemulsion, heat to 140-150° C., stir at 800-900 r / min for 0.5-1.5 h, and cool to room temperature to obtain a composite modified polyethylene wax nanoemulsion.
3. A modified starch slurry according to claim 2, characterized in that: In step A1, the ratio of phosphoric acid to ethanol is (2-3) g: (15-25) mL; In step A1, the amount ratio of calcium chloride dihydrate, ethanol, triethylamine, carboxylated cellulose nanofibers and ethanol solution of phosphoric acid is (4-5) g: (45-55) mL: (6-7) mL: (7-8) g: (5-6) mL.
4. A modified starch slurry according to claim 2, characterized in that: In step A2, the ratio of the maleic anhydride grafted polyethylene wax, sodium hydroxide and deionized water is (2-3) g: (1-2) g: (45-55) mL.
5. The modified starch slurry according to claim 2, characterized in that: In step A3, the ratio of the modified carboxylated cellulose nanofibers to the polyethylene wax nanoemulsion is (8-12) g:(90-120) mL.
6. The modified starch slurry according to claim 1, characterized in that: The modified corn starch is specifically prepared by the following steps: B1. Add corn starch to sodium phosphate buffer, stir evenly, add α-amylase and amyloglucosidase, and after enzymolysis, add sodium hydroxide solution, stir to kill the enzyme, centrifuge and dry to obtain porous starch; B2. Add curcumin and tannic acid to deionized water, stir evenly, add porous starch, shake at a rate of 120-130 r / min for 1-2 hours, centrifuge, and dry to obtain modified corn starch.
7. A modified starch slurry according to claim 6, characterized in that: In step B1, the amount ratio of corn starch, sodium phosphate buffer, α-amylase, amyloglucosidase and sodium hydroxide solution is (25-35) g: (80-120) mL: (0.1-0.3) g: (0.2-0.4) g: (4-6) mL.
8. The modified starch slurry according to claim 6, characterized in that: In step B2, the curcumin, tannic acid, deionized water and porous corn starch are used in a ratio of (2-3) g: (2-2.4) g: (25-35) mL: (8-9) g.
9. A method for preparing a modified starch slurry according to any one of claims 1 to 8, characterized in that: The method comprises the following preparation steps: Modified corn starch, wheat starch, potato starch, composite modified polyethylene wax nanoemulsion, coupling agent and emulsified oil are mixed, stirred at 75-85° C. for 20-30 minutes, then emulsified oil and coupling agent are added, stirred at a speed of 300-400 r / min for 20-30 minutes to obtain modified starch slurry.